2021
DOI: 10.1016/j.sdentj.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal risk assessment in a teaching hospital population in Saudi Arabia’s Eastern Province

Abstract: Objective With this cross-sectional study, we aimed to evaluate factors associated with moderate and high risk of periodontal disease (PD) progression in the Saudi population. Methods We reviewed 281 patients’ clinical charts from predoctoral periodontal clinics at the dental teaching hospital in the College of Dentistry (COD) at Imam Abdulrahman Bin Faisal University (IAU) in Dammam, Saudi Arabia. After obtaining ethical approval, we determined the Periodontal Risk Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Major risk factors associated with periodontitis include age, gender, oral hygiene, smoking status, ethnicity, lower socioeconomic status, and systemic diseases ( Nazir, 2017 , Madi et al, 2021 ). The relationships between PD and smoking, cardiovascular disease, diabetes mellitus, and adverse pregnancy outcomes have been reported extensively in the literature ( Albandar, 2002a , Albandar, 2002b , Nazir, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Major risk factors associated with periodontitis include age, gender, oral hygiene, smoking status, ethnicity, lower socioeconomic status, and systemic diseases ( Nazir, 2017 , Madi et al, 2021 ). The relationships between PD and smoking, cardiovascular disease, diabetes mellitus, and adverse pregnancy outcomes have been reported extensively in the literature ( Albandar, 2002a , Albandar, 2002b , Nazir, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous research that found males to be more likely to suffer from alveolar bone loss or periodontitis. 14,40 The causes of these gender differences are unknown; however, they may be related to males' poor compliance with oral hygiene practices. 43,44 Our study's limitations were that our sample size was relatively small and the fact that we only studied patients who visited a single dental hospital.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous research that found males to be more likely to suffer from alveolar bone loss or periodontitis. 14 40 The causes of these gender differences are unknown; however, they may be related to males' poor compliance with oral hygiene practices. 43 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these risk factors can be changed, but some others, such as age, gender, and ethnicity, cannot. After completing active periodontal therapy, most patients with periodontitis are still at risk of further disease progression or recurrence (3). Disease risk assessment scores integrate several variables with risk scales to provide a synthetic prediction value for every patient as well as a patient-risk stratification at a given follow-up time.…”
Section: Introductionmentioning
confidence: 99%